ChemInform Abstract: Access to Coumarins by Rhodium‐Catalyzed Oxidative Annulation of Aryl Thiocarbamates with Internal Alkynes. Issue 31 (August 2015) - Zhao, Yingwei; Han, Feng; Yang, Lei; Xia, Chungu
Abstract A wide range of 3, 4‐disubstituted coumarins are efficiently obtained by exploitation of a thiocarbamate group directed C—H bond activation, an annulation with an alkyne, and a desulfurization.